Metode Penginjilan Paulus dalam Perspektif 1 Korintus 9:19-23 Terhadap Masyarakat Multikultural dan Implikasinya Terhadap Penginjilan di Indonesia - Purba, Jhon Leonardo Presley; Saptorini, Sari (Sekolah Tinggi Teologi Kanaan Nusantara, 2020)
Paul was the most successful and greatest missionary in the history of Christianity, his evangelistic ministry covered a wide area, so Paul met various multicultural community groups in the first century. This study aims to study the methods of the apostle Paul's evangelism in the perspective of 1 Corinthians 9: 19-23 on the multicultural society of the first century and its implications for contemporary evangelism in Indonesia. This research is a qualitative descriptive study with a hermeneutic and literature study approach. Through this research, the writer tries to answer research problems by looking for literature sources that are correlated and relevant to the research problem. Thematic and exegetical approaches are used to describe the theological-historical foundation of the Apostle Paul's method of evangelism in the perspective of 1 Corinthians 9: 19-2, then describe the implications for contemporary evangelism in Indonesia. The result of this research is that the contextual evangelism method